2012
DOI: 10.1007/s10585-012-9461-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of non-anticoagulant heparin (S-NACH) on pancreatic cancer cell adhesion and metastasis in human umbilical cord vessel segment and in mouse model

Abstract: Metastasis is the most devastating aspect of cancer and it is the main cause of morbidity and mortality in cancer patients. Tumor cell adhesion to the vascular endothelial cell lining is an important step in metastatic progression and is prompted by platelets. Mucin 1 is over-expressed and aberrantly glycosylated in more than 60% of pancreatic ductal adeno-carcinomas, which mediate adhesion of pancreatic cancer cells to platelets via P-selectin. The anticoagulant low molecular weight heparins (LMWHs), which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…It was shown that the effect of S-NACH in inhibiting metastasis is not related to the heparin anticoagulant property as reported from our laboratory, and by others (14,15,24). These results indicate that the beneficial use of LMWH and its derivatives is not due to its anticoagulant activity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It was shown that the effect of S-NACH in inhibiting metastasis is not related to the heparin anticoagulant property as reported from our laboratory, and by others (14,15,24). These results indicate that the beneficial use of LMWH and its derivatives is not due to its anticoagulant activity.…”
Section: Discussionsupporting
confidence: 84%
“…Xenogen IVIS Living Image software (Caliper Life Sciences, version 3.2) was used to quantify non-saturated bioluminescence in regions of interest (ROI). Bioluminescence was quantified as photons/second for each ROI (15).…”
Section: Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 We also showed that S-NACH can interfere with the P-selectin-dependent binding of cancer cells to endothelial cells, both in vitro and in vivo. 23 In this study, we test the hypothesis that S-NACH via its antithrombotic effects and by interference with the Pselectin-dependent binding of sickled RBCs to endothelial cells will decrease the adhesion of sickle RBCs to the endothelial cells. By in vitro static adhesion assay, we show here for the first time that S-NACH decreases the increased adhesion of sickle RBCs to endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, a heparin-derived agent devoid of anticoagulant effect has been found to inhibit tumor growth via disruption of heparanase activity. Nonanticoagulant heparin S-NACH was also found to inhibit pancreatic cancer cell adhesion and metastasis [79]. In an animal study, heparin derivate showed anticancer and antiangiogenic effects [80].…”
Section: Heparin-derivative Agentsmentioning
confidence: 99%